Educational activities in the indigenous community: reports of monitoring experience (Research, Society and Development, 2020)
Objective: to report the experiences experienced through educational actions developed in the indigenous community by nursing academics, within the monitoring program. Methodology: This is a report of monitoring experience in the performance of the activities of nursing academics elaborated in the context of the discipline of Health of Indigenous Populations, Ethical-Racial and Riverine Nursing Graduation Course of a university center in the city of Manaus- Amazonas. Results: We carried out the planning of educational actions in the classroom and the division into groups composed of eight students. The themes proposed by them were: body hygiene for adolescents, breast cancer and uterus for women and hand hygiene for children. Conclusion: It is notorious the importance of this experience in the monitoring process, because it has provided a personal and professional growth of teaching practices.